Comparison of Fatwas on the Use of Menstrual Delay Medications for Women During Ramadan Between Dar al-Ifta' al-Misriyyah and the Indonesian Ulema Council (MUI) from the Perspective of Maqasid al-Shari’ah - Hakim, Abdul; Ahmad, Ridzwan; Syed Jaafar, Syed Mohd Jeffri (Millah: Journal of Religious Studies, 2025)
This study aims to compare the fatwa on the use of menstrual delay medicine for women in Ramadan issued by Dar al-Ifta' al-Misriyyah and the Indonesian Ulema Council (MUI) from the perspective of maqasid al-shari'ah. Both institutions play an important role in determining sharia law for Muslims in their respective countries. The main focus of this study is how the fatwas issued are in line with the principles of maqasid al-shari'ah, namely fulfilling the kulliyyat al-khams and i'tibar al-maal. The comparative method was used to analyse the similarities and differences in the legal approaches taken by these two institutions. Data collection was carried out through documentation and comparison methods, while data analysis was also carried out through descriptive qualitative methods by making maqasid al-shari'ah the main measuring stick. The result of the study shows that the fatwa of Dar al-Ifta' al -Misriyyah tends to be more open in allowing the use of drugs to delay menstruation in the month of Ramadan with certain conditions that prioritise health safety. In contrast, MUI's fatwa is more cautious, emphasises the health aspect as a priority, and does not recommend the use of period-delaying drugs in Ramadan except in emergencies. This difference reflects the diversity of understanding of maqasid al-shari'ah in responding to contemporary needs regarding women's acts of worship. It is hoped that the results of this study will provide a deeper understanding of the sharia implications of using a menstrual delay medicine in Ramadan and how maqasid al-shari'ah is applied in these fatwas.